2021
DOI: 10.1093/jas/skab102
|View full text |Cite
|
Sign up to set email alerts
|

Maternofetal inflammation induced for 2 wk in late gestation reduced birth weight and impaired neonatal growth and skeletal muscle glucose metabolism in lambs

Abstract: Intrauterine stress impairs growth and metabolism in the fetus and offspring. We recently found that sustained maternofetal inflammation resulted in intrauterine growth restricted fetuses (MI-IUGR) with asymmetric body composition, impaired muscle glucose metabolism, and β-cell dysfunction near term. These fetuses also exhibited heightened inflammatory tone, which we postulated was a fetal programming mechanism for the IUGR phenotype. Thus, the objective of this study was to determine whether poor growth and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 41 publications
4
40
0
Order By: Relevance
“…In the same way, maternal TNF-α concentration was inversely associated with birth weight in normal weight women ( 60 ). Human and animal studies also found that higher maternal plasma TNF-α concentration was associated with smaller birth weights ( 22 , 61 63 ). However, there are conflicting results, as other studies did not find correlations with either birth weight or fetal growth restriction ( 64 , 65 ).…”
Section: Discussionmentioning
confidence: 94%
“…In the same way, maternal TNF-α concentration was inversely associated with birth weight in normal weight women ( 60 ). Human and animal studies also found that higher maternal plasma TNF-α concentration was associated with smaller birth weights ( 22 , 61 63 ). However, there are conflicting results, as other studies did not find correlations with either birth weight or fetal growth restriction ( 64 , 65 ).…”
Section: Discussionmentioning
confidence: 94%
“…When IUGR fetal sheep were made hyperglycemic or hyperinsulinemic near term, whole-body glucose oxidation was decreased even though whole-body glucose utilization remained unchanged (Limesand et al, 2007;Brown et al, 2015). Subsequent sheep studies confirmed that the reduction in glucose oxidation rates were muscle-specific and persisted after birth (Cadaret et al, 2019b;Yates et al, 2019;Gibbs et al, 2021;Posont et al, 2021). Four-fold greater circulating lactate concentrations together with greater hepatic expression of gluconeogenic genes in IUGR fetal sheep (Brown et al, 2015) indicate that lactate produced in greater amounts by IUGR skeletal muscle supports hepatic glucose production.…”
Section: Nutrient-sparing Adaptations Reduce Muscle Glucose Metabolismmentioning
confidence: 99%
“…Offspring born with low birthweight due to IUGR initially continue to exhibit slower postnatal growth. For example, lambs born IUGR due to maternal heat stress or maternofetal inflammation remained about 20% smaller at 30 days of age, with comparable reductions in average daily gain ( Cadaret et al, 2019b ; Yates et al, 2019 ; Posont et al, 2021 ). As IUGR-born offspring reach the juvenile stage, many begin to exhibit postnatal catch-up growth, whereby their bodyweights equalize with uncompromised herdmates.…”
Section: Causes and Progression Of Iugrmentioning
confidence: 99%
See 2 more Smart Citations